Feather corticosterone reveals effect of moulting conditions in the autumn on subsequent reproductive output and survival in an Arctic migratory bird - Harms, N. Jane; Legagneux, Pierre; Gilchrist, H. Grant; Bêty, Joël; Love, Oliver P.; Forbes, Mark R.; Bortolotti, Gary R.; Soos, Catherine (Proceedings of the Royal Society B: Biological Sciences, 2014)
For birds, unpredictable environments during the energetically stressful times of moulting and breeding are expected to have negative fitness effects. Detecting those effects however, might be difficult if individuals modulate their physiology and/or behaviours in ways to minimize short-term fitness costs. Corticosterone in feathers (CORTf) is thought to provide information on total baseline and stress-induced CORT levels at moulting and is an integrated measure of hypothalamic-pituitary-adrenal activity during the time feathers are grown.We predicted that CORTf levels in northern common eider females would relate to subsequent body condition, reproductive success and survival, in a population of eiders nesting in the eastern Canadian Arctic during a capricious period marked by annual avian cholera outbreaks. We collected CORTf data fromfeathers grown during previousmoult in autumn and data on phenology of subsequent reproduction and survival for 242 eider females over 5 years. Using path analyses,we detected a direct relationship between CORTf and arrival date and body condition the following year. CORTf also had negative indirect relationships with both eider reproductive success and survival of eiders during an avian cholera outbreak. This indirect effect was dramatic with a reduction of approximately 30% in subsequent survival of eiders during an avian cholera outbreak when mean CORTf increased by 1 standard deviation. This study highlights the importance of events or processes occurring during moult on subsequent expression of life-history traits and relation to individual fitness, and shows that information from non-destructive sampling of individuals can track carry-over effects across seasons.